A perspective of making India robot ready: case study on Sakrobotix lab pvt. ltd. Issue 2 (2nd March 2021) - Mishra, Siwalik; Bhattacharya, Sonali
Abstract : Purpose: The purpose of this study is to identify and understand key strategies relating to the staffing, employee experience and employer branding of an inventive startup in robotics training and consumer robotics manufacturing space, keeping in mind the constraints and challenges faced by the company right from the beginning to date. Design/methodology/approach: A case-based method approach has been used. The Founder-Chief executive officer was interviewed multiple times. Interviews were transcribed for further analysis. Data was also sourced from the company website, news and digital media reports. Findings: Human resource strategies used by the company in venturing out in this niche market were explored and linked to the concepts of staffing, employee experience and employer branding. This case can be used for teaching the human resource challenges of a growing start-up. Practical implications: With the help of this case, readers may be able to appreciate the practice of critical concepts of staffing and employee experience in a growing startup. Originality/value: The premise of a budding start-up in a niche industry, such as robotics training in educational institutions and manufacturing of small-scale consumer robotics, adds to the novelty of the case.